1982
DOI: 10.1159/000182468
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for the Assessment of Bone Mass in Renal Osteodystrophy

Abstract: We have designed a method for the assessment of trabecular bone mass (TBM) in a central portion of L4 by means of CT scanning. A total of 29 normal individuals of different ages from both sexes, and 19 hemodialysis patients were studied. 3 selected patients were also studied 1 year later. A good in vivo reproducibility was demonstrated in a dog after repositioning. A positive inverse correlation was observed in the control group between age and TBM supporting the reliability of this method. As repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…TBBM has also previously been found to be reduced by 15-20% in uremic patients [ 18], though with a tendency for relative spinal preservation of bone mass. This con clusion is supported by a study using CT scanning of the lumbar spine [ 19] which found raised total bone mass in these patients, suggesting osteosclerosis. Total body cal cium determination using neutron activation analysis gives equivocal results [20][21][22], being generally normal or slightly raised compared to normals.…”
Section: Discussionsupporting
confidence: 56%
“…TBBM has also previously been found to be reduced by 15-20% in uremic patients [ 18], though with a tendency for relative spinal preservation of bone mass. This con clusion is supported by a study using CT scanning of the lumbar spine [ 19] which found raised total bone mass in these patients, suggesting osteosclerosis. Total body cal cium determination using neutron activation analysis gives equivocal results [20][21][22], being generally normal or slightly raised compared to normals.…”
Section: Discussionsupporting
confidence: 56%
“…Although total bone loss of 50-60% is the lower limit for detection by standard X-ray techniques [14], DEXA is capable of performing a noninvasive precise assessment of bone change and is thus a useful method to evaluate regional bone changes [1]. Mazess et al [7] reported that the BMD in HD patients was 20% lower than that of controls.…”
Section: Discussionmentioning
confidence: 99%
“…Facial nerve stimulation in response to activation of an electrode of a cochlear implant has been described, especially in patients with otosclerosis [8,14]. In these latter cases otospongiosis appears as foci of demineralization in the otic capsule [13].…”
Section: Introductionmentioning
confidence: 99%
“…An article of Torres and Moya in the M arch issue of your Journal [1] described a new method for determining bone mineral content in renal osteodystrophy by computerized tomography (CT). They emphasized the usefulness of eval uating trabecular bone mass for diagnosis of renal osteo dystrophy and for following the effects of any treatment given.…”
mentioning
confidence: 99%